Designing for Youth Engagement Across Formal and Informal Learning Networks - Thibaut, Patricia; Carvalho, Lucila (Proceedings of the International Conference on Networked Learning, 2018)
Growing up as part of a networked society is demanding youth’s active engagement in digital literacy practices – where their ability to find, evaluate, use, and create digital content is critical, as well as their ability to successfully participate in networks. Those with restrict access or those unable to effectively use technologies are unlikely to meaningfully contribute to a globalized world, with potential negative impact on individuals’ lives and on community prosperity. Understanding how to best design and encourage youth involvement in networked learning is therefore crucial. Drawing on the ACAD framework, this study examines the structural components of two learning networks geared at youth, within two learning scenarios: ‘in’ and ‘out’ of schools. By exploring the relationship between youth, tools, and spaces, we attempt to contribute to connect literature on formal and informal learning, digital culture and literacies. We also attempt to contribute to the call for understanding networked learning beyond the boundaries of Higher Education. Our research employs a case study methodology, conducted over consecutive weeks of a semester in two research sites: a year 10 classroom and a multiplayer online game called Potterworldmc. The asynchronous conversations of students on a social network site with learning purposes used at a school, as well as observations, interviews, and artefacts of a player were collected. The paper identifies key design elements and the emergent learning activity young people are engaging in, with a particular focus on digital literacy. We analyse the influence of social structures, tasks, tools and resources on youth activity, and discuss how previous boundaries between in-school and out-of-school, physical and digital spaces, traditional and new literacies might be rather blurred in learning networks geared at youth. We conclude by highlighting some key design elements across formal and informal networks.